2020
DOI: 10.1371/journal.pone.0231125
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of circulating-microRNA expression in lactating Holstein cows under summer heat stress

Abstract: Korean peninsula weather is rapidly becoming subtropical due to global warming. In summer 2018, South Korea experienced the highest temperatures since the meteorological observations recorded in 1907. Heat stress has a negative effect on Holstein cows, the most popular breed of dairy cattle in South Korea, which is susceptible to heat. To examine physiological changes in dairy cows under heat stress conditions, we analyzed the profiles circulating microRNAs isolated from whole blood samples collected under hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 57 publications
1
17
1
1
Order By: Relevance
“…miRNA sequencing in chronic heat stress showed that miR-199b was highly expressed and had the same expression tendency in this study [22]. miR-2284 families were also verified in circulating-miRNA expression in lactating Holstein cows under summer heat stress [23]. It suggested that miR-199b and miR-2284 families were related to heat stress response.…”
Section: Discussionsupporting
confidence: 65%
“…miRNA sequencing in chronic heat stress showed that miR-199b was highly expressed and had the same expression tendency in this study [22]. miR-2284 families were also verified in circulating-miRNA expression in lactating Holstein cows under summer heat stress [23]. It suggested that miR-199b and miR-2284 families were related to heat stress response.…”
Section: Discussionsupporting
confidence: 65%
“…On P13, miR-1246 and mir-23b-3p were found as upregulated in UF 6 . MicroR-1246 has been shown to play essential roles in the regulation of progesterone biosynthesis and corpus luteum 80 and has been related to the GO term post-embryonic development in our study. Reliszko et al also found increased levels of miR-23b in P16 serum samples in the pig 81 .…”
Section: Discussionmentioning
confidence: 60%
“…However, the exact function of the released miR-1246 in the target recipient cells under stress conditions needs more investigation. In correlation with GCs functions, predicted target genes of miR-1246 were known to play a role in progesterone biosynthesis regulation [ 45 , 46 ]. Moreover, a significant downregulation of miR-1246 expression was reported in large compared to small bovine follicles [ 47 ].…”
Section: Discussionmentioning
confidence: 99%